LC-MS-based phosphoproteomic profiling of the acute phase of myocardial infarction in mice - Yang GAO; Jian ZHANG; Shiyu HU; Jingpu WANG; Yiwen WANG; Jiatian CAO; Feng ZHANG (Zhongguo Linchuang Yixue, 2025)
ObjectiveTo investigate dynamic changes in myocardial protein phosphorylation during the acute phase of myocardial infarction (MI) in mice. MethodsSix 8-week-old C57BL/6J mice were randomly assigned to MI model (n＝3) or sham-operated control (n＝3) groups. Cardiac tissues were harvested 72 hours post-intervention for proteomic analysis. Phosphorylation modifications were systematically characterized using liquid chromatography-mass spectrometry (LC-MS). Bioinformatics analyses included differential phosphorylation screening, functional enrichment, hierarchical clustering, and protein-protein interaction network. ResultsLC-MS identified 1 921 differentially phosphorylated sites (20 tyrosine and 1 901 serine/threonine sites) across 851 proteins. Compared with controls, MI hearts exhibited significant phosphorylation upregulation at 1 545 sites and downregulation at 376 sites (P＜0.05). ConclusionsThis study delineates MI-associated phosphorylation dynamics, providing mechanistic insights and potential therapeutic targets for acute MI intervention.